Employee Motivation and Organizational Culture as Catalysts in Managing the Value of the Claremont Luxury Villa Rooms - Wayan Nurita; Gede Yoga Kharisma Pradana; Nyoman Agus Trimandala; Putu Sabda Jayendra (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
A quality organizational culture and high work motivation of villa employees can cause an increase in villa room occupancy rates. The Claremont Luxury Villas has, however, a room occupancy rate that tends to fall due to poor organizational culture and low work motivation of the employees. This research aims at analyzing the room occupancy value of The Claremont Luxury Villas. This research seeks to identify the causes of the decline in room occupancy rates and the catalyst for the room occupancy rates at The Claremont Luxury Villas. This research was completed using qualitative methods. The primary data source for this research was obtained through field studies at The Claremont Luxury Villas. Secondary research data sources come from related literature. Observations were applied to collect primary data and document studies to obtain secondary data. The collected data were qualitatively analyzed with the help of knowledge power relations theory and practice theory. The results of the research are: 1) Organizational culture and employee work motivation can be concluded as a catalyst for the occupancy value of The Claremont Luxury Villa rooms; 2) The continuously deteriorating performance of organizational culture and increasingly low levels of employee motivation at work have resulted in a decline in the room occupancy rate at The Claremont Luxury Villa.